A Preliminary Study on Promoting Contextual Teaching and Learning Using Smart Water Quality Sensors - Sulisworo, Dwi; Fitrianawati, Meita; Subrata, Arsyad Cahya; Kalid, Khairul Shafee; Wan Ahmad, Wan Fatimah (Indonesian Review of Physics, 2023)
Building awareness among students on the issues of natural environmental phenomena has always been a challenge due to the difference in location between the student and the observed phenomena. The issues of the natural environment have been a part of the curriculum in elementary schools. One of the lessons taught on the natural environment in elementary schools is related to the water conditions in various areas filled with water, such as ponds, rivers, lakes, etc. Currently, learning in the natural environment is based on text, images, and videos, and learning activities using real-time data are still rare. This study presents the development of an IoT-based Smart Water Quality application prototype. The prototype consists of conductivity, pH, oxygen levels, salinity, and turbidity sensors. The IoT prototype can also be used to automatically monitor fish, shrimp, and other species in aquaculture ponds. Using the IoT-based Smart Water Quality application prototype, teachers can enhance students' higher-order thinking skills by designing learning activities using real-time data to identify, compare, and classify various concepts or phenomena.